Assessment the Levels of Depression among Patients with Hemodialysis at the Dialysis Centers in Mosul City - Ahmed Abdel-Qader Suleiman, Sarmad Muqdad Abed, Salim Shihab Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Depression is the most common psychiatric illness in patients with end-stage renal disease . Objectives: a descriptive study design, aiming to assess the levels of depression among patients with hemodialysis at two dialysis centers in Mosul City for the period 1st January to 15the Jun 2023. Material and Methods: The study used a non-probability accidental sampling method, 84 patients with Chronic Kidney Disease who were subjected to hemodialysis was enrolled in two dialysis centers at Mosul City. The study was conducted using the diagnostic poll method and standardized research tools: Part 1 collected socio-demographic characteristics of the patients. Part 2 [the Center for Epidemiologic Studies Depression Scale (CESD-R-20)], a 20-item self-report questionnaire to measure depressive symptoms. The scale had a 4-level Likert scale, and a total score was calculated by summing the 20 items. Scores equal to or above 16 indicated a person at risk for clinical depression. Data were collected through self-report questionnaires. Conclusion: The findings indicated varying levels of depression among the patients, with some experiencing high levels of depression symptoms. Recommendation: The study provides valuable insights about the need for coordination between mental health professionals and dialysis patients in dialysis centers. Keywords: Hemodialysis, depression, patient.